Living with the Genie : essays on technology and the quest for human mastery - Lightman, Alan P., 1948-; Sarewitz, Daniel R.; Desser, Christina (Island Press, 2003)
"Science and technology continually transform our experience and society in ways that often seem to be beyond our control. Today different areas of research and innovation are advancing synergistically and multiplying the rate and magnitude of technological and societal change. As the power of technology continues to accelerate, who will be the master of whom?" "In Living with the Genie, leading writers and thinkers come together to confront this question from many perspectives, through provocative essays that open the door to a new dialogue on how technology may be changing what it means to be human, in ways we scarcely comprehend"--Publisher description